Really big numbers - Schwartz, Richard Evan (Providence, Rhode Island : AMS, American Mathematical Society, 2014)
The book begins with small, easily observable numbers before building up to truly gigantic ones, like a nonillion, a tredecillion, a googol, and even ones too huge for names! Any person, regardless of age, can benefit from reading this book. Readers will find themselves returning to its pages for a very long time, perpetually learning from and growing with the narrative as their knowledge deepens. Really Big Numbers is a wonderful enrichment for any math education program and is enthusiastically recommended to every teacher, parent and grandparent, student, child, or other individual interested in exploring the vast universe of numbers.
Text in English.
Keywords: Number concept -- Juvenile literature; Numbers, Real -- Juvenile literature